Predictive Factors of Inadvertent Durotomy in Lumbosacral Prolapsed Intervertebral Disc Surgeries: A Retrospective Review at a Tertiary Care Centre in India - Carvalho, Ajay Sebastian; Yadav, Kishan Kumar; MN, Arjun; Kumar, Ashok; Shivashankar, Roopa; Gupta, Vijay Kumar (Nepal Journal of Neuroscience, 2020)
Introduction: Inadvertent dural tear is an undesirable intraoperative complication of spine surgery, with a reported incidence range of 1.7% to 17%. The purpose of this study is to determine the predictive factors of inadvertent durotomies (ID) in lumbosacral prolapsed disc surgeries and suggest a scoring system for pre-operative assessment of these predictors. Methods and Materials: This is a retrospective observational study done in 230 patients operated for prolapsed lumbar intervertebral discs, between January 2010 to November 2012. The inadvertent dural tears were grouped as unrecognised, simple and complicated. Data were collected regarding diagnosis, comorbidities, surgical procedure, operating surgeon, prior spine surgeries, type of ID and complications. Results: Of the 230 patients, ID was seen in 6.5 % (15 patients). Higher incidences were noted in elderly (33.3%) and obese (7.6%). Bone nibbler and Kerrison’s rongeur were the most common tools associated. Redo surgeries have a significant higher incidence (12.9%) as compared to the first surgery (5.53%). Conclusions: The risk of ID in prolapsed lumbar intervertebral disc surgeries is high in presence of bony and ligamentous canal stenosis, instrument handling, and in smaller size of incisions. Additionally, elderly age of patients, obesity and surgeon fatigue appears to be a major determinant. Conscious effort to prevent this complication during surgery by predicting risks pre-operatively using a scoring system can aid in preventing ID.